MODERN APPROACHES TO SEGMENTATION OF MANAGEMENT ACCOUNT - Elena A. Sharovatova (Advanced Engineering Research)
The accounting entities expansion is offered. The necessity of the allocation of six management segments whose accounting information will permit to form the development strategy of the branch business is proved.